Global, regional, and national temporal trends in prevalence, deaths and disability-adjusted life years for chronic pulmonary disease, 1990–2021: an age-period-cohort analysis based on the global burden of disease study 2021 - Cao, Wubing; Zheng, Jun; Li, Qun; Guo, Dabin; Fan, Xianzhi; Zhu, Guoning; Yuan, Xiao (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality globally, with significant disparities in disease burden across countries and socioeconomic regions. Despite advancements in public health, the global burden of COPD remains substantial, particularly in low- and middle-income countries. This study aims to provide a comprehensive analysis of global, regional, and national trends in COPD-related prevalence, deaths, and disability-adjusted life years (DALYs) from 1990 to 2021 using an age-period-cohort (APC) model.MethodsData from the Global Burden of Disease Study 2021 were analyzed for 204 countries and territories, stratified by five Sociodemographic Index (SDI) levels. An APC model was employed to assess the temporal effects of age, time periods, and birth cohorts on COPD burden. Trends in prevalence, deaths, and DALYs were evaluated through metrics such as Net Drift, Local Drift, and risk ratios.ResultsGlobally, from 1990 to 2021, the age-standardized rates of COPD demonstrated a decline of −1.46% (95% UI: −3.36 to 0.39%) in prevalence, −37.12% (95% UI: −43.37% to −27.68%) in deaths, and −36.98% (95% UI: −42.37% to −28.54%) in DALYs. After adjusting for age and cohort effects, the annual changes were −0.35% (95% UI: −0.39% to −0.32%) in prevalence, −3.87% (95% UI: −4.00% to −3.74%) in deaths, and − 2.95% (95% UI: −3.02% to −2.89%) in DALYs. Notably, in middle, low-middle, and low SDI regions, the age-standardized prevalence rates in 2021 showed an increase compared to 1990, with respective changes of 4.03% (95% UI: 2.00–5.89%), 0.13% (95% UI: −2.90 to 2.84%), and 6.71% (95% UI: 4.25–8.91%). However, age-standardized deaths and DALYs significantly decreased across all five SDI regions. From an age effect perspective, globally, over 50% of COPD prevalence is concentrated among individuals aged 65 years and older, particularly in middle, low-middle, and high-middle SDI regions. COPD-related deaths and DALYs have shown a declining trend across all age groups. Globally, the period effect indicates that earlier periods were associated with a higher burden of disease, while cohort effects highlight that birth cohorts around 1920 had a particularly pronounced impact on the COPD burden. Both period and cohort effects exhibited notable heterogeneity across different SDI regions and countries,ConclusionThe prevalence of COPD remains concerning. Compared to 1990, the global prevalence of COPD in 2021 showed a stable or slightly increasing trend, with over half of the countries experiencing an annual increase in prevalence during the 1990–2021 period. Global mortality and DALYs associated with COPD showed a notable decline in 2021 compared to 1990. However, this trend exhibited significant heterogeneity across countries and regions, likely linked to differences in socioeconomic development. Countries in the high-middle and middle SDI regions were found to be more affected by period effects. From an age effect perspective, population aging has undoubtedly exacerbated the COPD burden. Regarding cohort effects, earlier birth cohorts demonstrated a stronger contribution to the increasing disease burden. While Higher levels of socioeconomic development can mitigate the adverse effects associated with earlier birth cohorts.